If f(x) = eˣ and g(x) =
, then show that fog = gof and find f⁻¹ and g⁻¹.
Answers
Answered by
1
Answer:
fog = gof
Step-by-step explanation:
In the attachments I have answered this problem.
Concept:
If f and g are two functions such that
fog = gof = I where I is identity function then inverse of f = g and inverse of g = f.
See the attachment for detailed solution.
Attachments:
![](https://hi-static.z-dn.net/files/d6a/88c69586ab911abd6e348e8b3799efde.jpg)
![](https://hi-static.z-dn.net/files/d43/73b47ed9a730b3570ae5315967f904ce.jpg)
Answered by
1
Step by step Explanation:
As we know that fog(x) = f(g(x))
![fog(x) = {e}^{ log_{e}(x) } = x \\ \\ gof(x) = log_{e}( {e}^{x} ) = x \\ \\ fog(x) = {e}^{ log_{e}(x) } = x \\ \\ gof(x) = log_{e}( {e}^{x} ) = x \\ \\](https://tex.z-dn.net/?f=fog%28x%29+%3D+%7Be%7D%5E%7B+log_%7Be%7D%28x%29+%7D+%3D+x+%5C%5C+%5C%5C+gof%28x%29+%3D+log_%7Be%7D%28+%7Be%7D%5E%7Bx%7D+%29+%3D+x+%5C%5C+%5C%5C+)
since log and exponential cancels each other.
Finding f inverse:
![y = f(x) \\ \\ y = {e}^{x} \\ \\ log \: y = log \: {e}^{x} \\ \\ x = log \: y \\ \\ x = f(y) \\ \\ {f}^{ - 1}( x) = log_{e}\: x y = f(x) \\ \\ y = {e}^{x} \\ \\ log \: y = log \: {e}^{x} \\ \\ x = log \: y \\ \\ x = f(y) \\ \\ {f}^{ - 1}( x) = log_{e}\: x](https://tex.z-dn.net/?f=y+%3D+f%28x%29+%5C%5C+%5C%5C+y+%3D+%7Be%7D%5E%7Bx%7D+%5C%5C+%5C%5C+log+%5C%3A+y+%3D+log+%5C%3A+%7Be%7D%5E%7Bx%7D+%5C%5C+%5C%5C+x+%3D+log+%5C%3A+y+%5C%5C+%5C%5C+x+%3D+f%28y%29+%5C%5C+%5C%5C+%7Bf%7D%5E%7B+-+1%7D%28+x%29+%3D+log_%7Be%7D%5C%3A+x)
Finding g inverse:
![y = g(x) \\ \\ y = log_{e}(x) \\ \\ {e}^{y} = {e}^{ log_{e}(x) } \\ \\ x = {e}^{y} \\ \\ {g}^{ - 1} (x) = {e}^{x} \\ y = g(x) \\ \\ y = log_{e}(x) \\ \\ {e}^{y} = {e}^{ log_{e}(x) } \\ \\ x = {e}^{y} \\ \\ {g}^{ - 1} (x) = {e}^{x} \\](https://tex.z-dn.net/?f=y+%3D+g%28x%29+%5C%5C+%5C%5C+y+%3D+log_%7Be%7D%28x%29+%5C%5C+%5C%5C+%7Be%7D%5E%7By%7D+%3D+%7Be%7D%5E%7B+log_%7Be%7D%28x%29+%7D+%5C%5C+%5C%5C+x+%3D+%7Be%7D%5E%7By%7D+%5C%5C+%5C%5C+%7Bg%7D%5E%7B+-+1%7D+%28x%29+%3D+%7Be%7D%5E%7Bx%7D+%5C%5C+)
Hope it helps you
As we know that fog(x) = f(g(x))
since log and exponential cancels each other.
Finding f inverse:
Finding g inverse:
Hope it helps you
Similar questions